Turnover intention among Lebuhraya Shapadu Sdn. Bhd. workers / Noor Suziana Saharudin - Saharudin, Noor Suziana (Faculty of Business and Management, 2009)
Retention and productivity levels of a workforce are one of the essential ingredients for organizations to prosper in today’s competitive business environment. Turnover intentions of the workforce are an important consideration for managers of organizations, employees, families, and communities alike. This study investigated a comprehensive model of turnover intentions that included four variables, (organizational commitment, work strain, work overload, and work-family conflict with the turnover intentions. The objective of this study is to identify the relationship between organizational continuance commitments, work overload, work strain and work-family conflict with turnover intentions of employees. A structured questionnaire was distributed personally and completed by 50 respondents of the employees at the Lebuhraya Shapadu Sdn Bhd. Results shows that organization continuance commitment and works train are do not have a relationship with turnover intention, while work overload and work-family conflict were correlated with turnover intentions, it’s mean it have a relationship with turnover intention. The major recommendations for this research are that managers of organization need to implementation of high-performance work practices within their organization to reduce turnover intentions. In the final chapter, the conclusions are discussed in terms of its practical implications to organizations overcome the problems, employees and the need for future research.